On Soft \(ω\)-Connectedness in Soft Topological Spaces - Rathee, Savita; Girdhar, Ridam (Communications in Mathematics and Applications, 2021)
This article aims to define soft \(ω\)-connected space and soft \(ω\)-disconnected space in soft topological spaces. We study the characteristics of these spaces with appropriate examples and discuss their relation with soft connected and soft disconnected spaces.